Highly hydrophobic isoreticular porous metal-organic frameworks for the capture of harmful volatile organic compounds - Padial, Natalia M.; Quartapelle Procopio, Elsa; Montoro, Carmen; Lopez, Elena; Enrique Oltra, J.; Colombo, Valentina; Maspero, Angelo; Masciocchi, Norberto; Galli, Simona; Senkovska, Irena; Kaskel, Stefan; Barea, Elisa; et al. (Angewandte Chemie International Edition, 2013)
Tunable hydrophobicity: Efficient air filters for the protection against chemical warfare agents might be achieved by surface functionalization of the pores in robust metal-organic frameworks (MOFs) with fluoroalkyl residues and the precise control of their pore size (see picture). These MOFs capture harmful volatile organic compounds even under extremely moist conditions (80 % relative humidity). Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: air filters; chemical warfare agents; gas chromatography; metal-organic frameworks; X-ray diffraction